Best practices of judicial governance: A scoping review protocol - Leandra Vilela Rodrigues Chaves; Marcos de Moraes Sousa; Woska Pires da Costa; Jéssica Traguetto; Flávio Manoel Coelho Borges Cardoso; Miguel de Matos-Torres (PLoS ONE, 2025)
Background Enhancing performance in the public sector is closely tied to institutional structures, governance models, and the behavior of public officials. In the Judiciary, these factors significantly affect the effectiveness of court administration and justice delivery. Judicial governance is a complex and evolving concept encompassing standards and practices related to accountability, independence, resource management, and institutional performance, progressively integrating principles from public management reforms. Despite its growing relevance, the field remains fragmented, with limited evidence connecting international standards to best governance practices in judicial administration. Objective This protocol outlines a scoping review designed to identify, map, and synthesize evidence on best practices in judicial governance, examining their relationship with the effective administration of justice and identifying research gaps to propose a future research agenda. Method This review will follow the JBI methodology and the PRISMA-ScR guidelines. A comprehensive search will be conducted in databases such as Scopus, Web of Science, DOAJ, and JSTOR, as well as additional searches in grey literature. The PCC (Population, Concept, and Context) framework guided the eligibility criteria, and the PRESS 2015 checklist was used to validate the search strategy. The PRISMA-S checklist will inform the reporting of the search process. Studies of all designs and publication statuses will be considered, with no restrictions on language or publication date. Two reviewers will independently screen using Rayyan software, with a third reviewer resolving any disagreements. Data extraction will occur at two levels: general source information and specific content related to the review scope. Qualitative data will be analyzed using NVivo software, enabling categorization, descriptive synthesis, gap identification, and the development of a research agenda. Discussion This scoping review aims to generate key evidence that can inform institutional standards and best governance practices to support evidence-based policymaking; while it does not assess the risk of bias, its systematic methodology and inclusion of grey literature enhance its relevance for future research and innovations in the justice sector. Through this scoping review, key evidence will generate insights that can enhance institutional standards and best practices in governance, enabling evidence-based policymaking. Although the review does not assess the risk of bias, its systematic approach and inclusion of grey literature strengthen its potential to support future research and governance innovations in the justice sector. Trial registration OSF Registries, Jan 21, 2024: https://doi.org/10.17605/osf.io/agv3b.